2012
DOI: 10.3109/17435390.2011.652205
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube compared with carbon black: effects on bacterial survival against grazing by ciliates and antimicrobial treatments

Abstract: The ingestion and digestion of Escherichia coli by the ciliated protozoan, Tetrahymena thermophila, was investigated after an initial exposure to either water-soluble single-walled carbon nanotubes (SWNT) or to carbon black (CB). Both SWNT and CB were internalised and visible in food vacuoles of ciliates. When presented with E. coli expressing green-fluorescent protein (GFP), these ciliates internalised bacteria as well. However, ciliates that had first internalised SWNT but not CB subsequently externalised or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Additionally, the information collected to the NanoE-Tox database indicated that ENMs were readily ingested by different organisms [55,72,77,[119][120][121][122][123]192,[194][195][196][197][198][199][200][201][202] and tended to accumulate in them [55,59,60,[69][70][71]84,[122][123][124][125][126]159,[176][177][178][179]187,189,192,[201][202][203][204][205][206][207][208][209][210][211]…”
Section: Mechanism Of Toxic Actionmentioning
confidence: 99%
“…Additionally, the information collected to the NanoE-Tox database indicated that ENMs were readily ingested by different organisms [55,72,77,[119][120][121][122][123]192,[194][195][196][197][198][199][200][201][202] and tended to accumulate in them [55,59,60,[69][70][71]84,[122][123][124][125][126]159,[176][177][178][179]187,189,192,[201][202][203][204][205][206][207][208][209][210][211]…”
Section: Mechanism Of Toxic Actionmentioning
confidence: 99%
“…Increased use of nanomaterials, including CNT, increases the likelihood that microorganisms used in industrial processes will also be affected, which may be a problem for e.g. wastewater treatment plants [106,107,112]. …”
Section: Effects In Living Organismsmentioning
confidence: 99%
“…Accumulation of fecal pellets in the medium was not evident in the images of T. thermophila grown in rich medium (Figure 2), indicating that MWCNTs were excreted as aggregates that were small enough for reuptake, resulting in a higher percentage of administered MWCNTs in the protozoan population (Figure 3). Comparatively, Chan et al 41 showed that initial ingestion of subtoxic amounts of SWCNTs by T. thermophila impaired subsequent digestion of Escherichia coli and increased the number of egested fecal pellets. Here, grazing on MWCNT-amended P. aeruginosa did not appear to alter the numbers of fecal pellets compared to control cultures (Figures 4 and S7).…”
Section: Resultsmentioning
confidence: 99%